presidential decree law No. 23/2015 Amending certain provisions of the Building law and its promulgating law no 119/2008 - Egypt (2025)
Presidential Decree-Law no. 23 of the year 2015 amending certain provisions of the building law and its promulgating law No. 119 of the year 2008 قرار رئيس جمهورية مصر العربية بالقانون رقم 23 لسنة 2015 بتعديل بعض أحكام قانون البناء والقانون الصادر به رقم 119 لسنة 2008